Sulfonated melanin derivatives: theoretical evaluation of local reactivities and chemical structures - Cuba, João P. B. [UNESP] (2021)
Melanins are natural macromolecules present in several organisms responsible for photoprotection, photosensitivity, ion chelation, and thermoregulation. Such materials have attracted attention due to their interesting electronic properties, which suggest their possible application in biocompatible devices. However, the low typical solubility of traditional melanins does not allow the production of good quality thin films. In this sense, soluble compounds obtained via alternative synthetic routes, for instance, via levodopa (L-DOPA) oxidation in sulfonated solvents (S-melanins), can be considered interesting technological materials. Despite this, the structural and electronic features of these compounds are not fully understood. In this context, here we present a theoretical study on the local reactivities of S-melanin building blocks to better understand possible mechanisms involved in its synthesis and propose extended structures of this material. For this purpose, condensed-to-atoms Fukui indices were evaluated in the framework of the density functional theory (DFT). The obtained results show that the different side groups present in S-melanins do not significantly influence the reactivity of the compound in relation to non-functionalized melanins, indicating that both materials can present similar macroscopic structures. Graphical abstract: [Figure not available: see fulltext.].